Maritime societies of the Viking ad medieval world (Leeds)
xii, 396 s.
Keywords: "This book is a study of communities that drew their identity and livelihood from their relationships with water during a pivotal time in the creation of the social, economic and political landscapes of northern Europe. It focuses on the Baltic, North and Irish Seas in the Viking Age (AD 790–1050) and early Middle Ages (AD 1050–1200), with a few later examples (such as the Scottish Lordship of the Isles) included to help illuminate less well-documented earlier centuries. Individual chapters introduce maritime worlds ranging from the Isle of Man to Gotland — while also touching on the relationships between estate centres, towns, landing places and the sea in the more terrestrially oriented societies that surrounded northern Europe's main spheres of maritime interaction. It is predominately an archaeological project, but draws no arbitrary lines between the fields of historical archaeology, history and literature. The volume explores the complex relationships between long-range interconnections and distinctive regional identities that are characteristic of maritime societies, seeking to understand communities that were brought into being by their relationships with the sea and who set waves in motion that altered distant shores." --